"Admiral´s night" by Machado de Assis: a suburban people - Silva, Eufrida Pereira da (Via Atlântica, 2022)
Admiral´s Night", by Machado de Assis, was published in 1884 in Rio de Janeiro's Gazeta de Notícias and in Histórias sem Data in the same year. In the short story, a love triangle is experienced by suburban people like Genoveva, Deolindo and José Diogo. Deolindo, when he learned that he was betrayed, he who swore love, started making promises of death. The frivolous character of the girl, the farce of the admiral's night and the unpredictable life of the peddler around the world form a vortex that collides with the ideals of the inaugural speeches of a newly independent nation with pretensions of unity, civilization and order. The discussion is treated according to Schwarz (2000), DaMatta (1997), Candido (1970) and Schwarcz (2000).